Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1302/0301-620x.98b3.36904
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for patients with a fracture of the hip in major trauma centres

Abstract: There is no evidence that reconfiguring major trauma services in England disrupted the treatment of older adults with a fracture of the hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Although there was a reconfiguration of major trauma services in England (but not Scotland) from April 2012, this did not have a measurable effect on the quality of hip fracture care. 46 Second, we did not have access to some variables, such as LOS, in Scottish data and so were limited to undertaking ITSA without a control region for these outcomes. As discussed above, the absence of a control can result in erroneous attribution of change to a single intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a reconfiguration of major trauma services in England (but not Scotland) from April 2012, this did not have a measurable effect on the quality of hip fracture care. 46 Second, we did not have access to some variables, such as LOS, in Scottish data and so were limited to undertaking ITSA without a control region for these outcomes. As discussed above, the absence of a control can result in erroneous attribution of change to a single intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 A sufficient volume of scientific data exists with regard to surgical treatment, applicable methods, and mortality. 3 , 9 In contrast, in-depth analyses regarding complications, particularly infections, are rare. 5 , 11 , 12 Furthermore, a review of national arthroplasty registries showed that revisions due to hematoma do not have priority and are not reported in many publications.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment of proximal femoral fractures is predominantly performed in geriatric patients; thus, it is associated with high morbidity and mortality. 1 4 A variety of surgical techniques are available, including intramedullary nails, dynamic hip screws, and alloarthroplasty, the use of which depends on the patient’s age and fracture morphology. 1 4 Studies involving a high numbers of cases or national registries have reported revision rates of 6% to 15% and a 1-year mortality of up to 30%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have different clinical requirements compared with major trauma patients. 13,14 While the care of these patients has not been adversely effected by the introduction of major trauma centres, 15 it remains unclear whether outcomes for hip fractures can be improved by the separation of their care into dedicated units away from the regionalised trauma centres.…”
Section: Introductionmentioning
confidence: 99%